PRODUCTIVITY AND COST ANALYSIS OF DRILLING FOR BLAST HOLES IN GRANITE MINING AT PT. HANSINDO MINERAL PERSADA - Prayitno, Dwi Angga; Syahrudin, Syahrudin; Syafrianto, M. Khalid (Jurnal Teknik Sipil, 2024)
Granite's durability makes it a popular choice in construction, but efficient granite mining, especially through drilling for blast holes, is essential for productivity and cost management. PT. Hansindo Mineral Persada in Kalimantan Barat faces challenges balancing drilling efficiency and costs, requiring a detailed study to optimize operations. This article presents a study analyzing drilling machine productivity, focusing on the rotary-percussive method based on 2022 drilling costs. The study revealed insights into drilling productivity, obstacles, and costs. Notably, productivity, measured by Net Penetration Rate (NPR) and Gross Penetration Rate (GPR), showed significant improvements: NPR for machine 001 increased from 71.39 m ³/hour to 95.24 m ³/hour, and GPR from 58.02 m ³/hour to 75.35 m ³/hour. Machine 002"™s NPR improved from 53.49 m ³/hour to 60.22 m ³/hour, with GPR rising from 44.47 m ³/hour to 46.25 m ³/hour. Avoidable obstacles decreased, but unavoidable ones persisted. Drilling costs varied, with machine 001"™s cost decreasing from Rp 68,857 to Rp 58,873 per meter and machine 002"™s increasing from Rp 81,324 to Rp 86,022. Recommendations include improved planning, regular maintenance, and better scheduling. Future research on rock properties, equipment age, and tool quality could further enhance productivity and efficiency.